(untitled) (Journal of history, 2019)
Аuthors of the article conditionally divided the historiography into two groups: survey studies; special works devoted to the study of sources. Based on the analysis, the researchers determined the features of the assessment of the Mongolian religious policy. They defined the researcher’s approach to this problem. In the article it was characterized the conceptual approach and was carried out a comparative analysis of the religious policy of the Mongols in the modern period. It is shown that the conclusions of the authors became the foundation for subsequent works in this direction. It was made an attempt to show the continuity of scientific views and those aspects of this problem that have yet to be revealed. Despite the small number of works and their specificity, we can say that pre-revolutionary historians managed to solve a number of complex problems: it was formulated a more or less objective view of the religious policy of the Mongol khans; at the result of the introduction of a large number of different sources into scientific circulation, it was formed a critical view of the problem; there was an understanding that the relationship of the Mongol khans with the conquered peoples was not unambiguous; methods of studying history (positivism) appeared; a calmer view of the activities of the Mongol rulers, including in the field of religious policy, has taken shape.